Citizen Science and Social Innovation: Mutual Relations, Barriers, Needs, and Development Factors - Andrzej Klimczuk; Egle Butkeviciene; Minela Kerla (Frontiers Media SA, 2022)
Social innovations are usually understood as new ideas, initiatives, or solutions that make it possible to meet the challenges of societies in fields such as social security, education, employment, culture, health, environment, housing, and economic development. On the one hand, many citizen science activities serve to achieve scientific as well as social and educational goals. Thus, these actions are opening an arena for introducing social innovations. On the other hand, some social innovations are further developed, adapted, or altered after the involvement of scientist-supervised citizens (laypeople or volunteers) in research and with the use of the citizen science tools and methods such as action research, crowdsourcing, and community-based participatory research. Such approaches are increasingly recognized as crucial for gathering data, addressing community needs, and creating engagement and cooperation between citizens and professional scientists. However, there are also various barriers to both citizen science and social innovation. For example, management, quality and protection of data, funding difficulties, non-recognition of citizens' contributions, and limited inclusion of innovative research approaches in public policies. In this volume, we open theoretical as well as empirically-based discussion, including examples, practices, and case studies of at least three types of relations between citizen science and social innovation: (1) domination of the citizen science features over social innovation aspects; (2) domination of the social innovation features over the citizen science aspects; and (3) the ways to achieve balance and integration between the social innovation and citizen science features. Each of these relationships highlights factors that influence the development of the main scales of sustainability of innovations in the practice. These innovations are contributing to a new paradigm of learning and sharing knowledge as well as interactions and socio-psychological development of participants. Also, there are factors that influence the development of platforms, ecosystems, and sustainability of innovations such as broad use of the information and communications technologies (ICTs) including robotics and automation; emerging healthcare and health promotion models; advancements in the development and governance of smart, green, inclusive and age-friendly cities and communities; new online learning centers; agri-food, cohousing or mobility platforms; and engagement of citizens into co-creation or co-production of services delivered by public, private, non-governmental (NGOs) organizations as well as non-formal entities.
Keywords: I28; O31; O35; O38; Q55; 330; advocacy; big data; citizen science; civil society; co-creation and co-production; crowdsourcing; data management; digital platforms; empowerment; environmental issues; ethics; evaluation and monitoring; governance; health promotion; ICTs; impact assessment; local and regional development; multidisciplinarity; NGOs; open science; participatory research; public engagement; public health; public policy; resilience building; science communication and dissemination; science policy and research funding; smart technologies; social capital; social entrepreneurship; social innovation; social problems; sustainability in science; technological innovation; volunteering